Public procurement and revolving doors: An assessment of the Finnish legislation - Herzig, Mikko (My University, 2021)
Revolving doors -the phenomenon of public officials moving from the public to the private sector and vice versa, has been frequently in the news recently. Switching could have significant effects on public procurement through conflicts of interest. This thesis assesses the Finnish legislation by answering the question: Is the Finnish legislation sufficient for the regulation of revolving doors in public procurement? The thesis provides the answer in three parts: 1) An economical assessment of revolving doors, their effects and impacts on public procurement. 2) Analysis of the current Finnish legal system regarding revolving doors in public procurement using both EU and national sources. 3) Evaluating the current legislation against the effects of revolving doors found in part one. Overall, the answer to the research question is likely to be negative and therefore various policy recommendations and questions for future research are discussed.